Phosphorylation controls the functioning of Staphylococcus aureus isocitrate dehydrogenase – favours biofilm formation. (August 2015) - Venkateswara Prasad, U.; Vasu, D.; Yeswanth, S.; Swarupa, V.; Sunitha, M. M.; Choudhary, A.; Sarma, P. V. G. K.
Abstract Isocitrate dehydrogenase (IDH) gene from Staphylococcus aureus ATCC12600 was cloned, sequenced and characterized (HM067707). PknB site was observed in the active site of IDH; thus, it was predicted as IDH may be regulated by phosphorylation. Therefore, in this study, PknB, alkaline phosphatase III (SAOV 2675) and IDH genes (JN695616, JN645811 and HM067707) of S. aureus ATCC12600 were over expressed from clones PV 1, UVPALP-3 and UVIDH 1. On passing the cytosloic fractions through nickel metal chelate column, pure enzymes were obtained. Phosphorylation of pure IDH by PknB resulted in the complete loss of activity and was restored upon dephosphorylation with SAOV 2675 which indicated that phosphorylation and dephosphorylation regulate IDH activity in S. aureus. Further, when S. aureus ATCC12600 was grown in BHI broth, decreased IDH activity and increased biofilm units were observed; therefore, this regulation of IDH alters redox status in this pathogen favouring biofilm formation.